THE EFFECT OF LEVERAGE (DER) AND PROFITABILITY (ROE AND EPS) ON THE SHARE PRICE OF PT KIMIA FARMA TBK FOR THE 2014-2023 PERIOD - Agustina, Siti Fadhilah; Herlinawati, Erna (Dynamic Management Journal, 2025)
This research examines the influence of leverage (Debt to Equity Ratio - DER) and profitability (Return on Equity - ROE and Earnings Per Share - EPS) on the stock price of PT Kimia Farma Tbk during the period 2014-2023. The study employs a quantitative approach, utilizing secondary data from financial reports and investment websites. This study shows that stock price fluctuated significantly, especially during the COVID-19 pandemic which increased demand for pharmaceutical product. However, DER increased substantially, indicating the company’s dependence on debt financing. Meanwhile, ROE and EPS produced negative values, indicating challenges in generating profits relative to equity. The result showed that although DE, ROE, and EPS had as significant effect on stock price, simultaneously DER, ROE, and EPS had a significant effect on stock price. This study shows the importance of understanding financial ratios in guiding investment decisions amid market volatility and economic uncertainly, especially during the COVID-19 pandemic which has a significant impact on the pharmaceutical sector.